Analisa Audit Sistem Informasi Barang atau Jasa Menggunakan COBIT 5.0 - Miftakhul Jannah; Besus Maula Sulthon (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
Kirana windu is a company engaged in rubber management and has implemented an information system in the inventory section which aims to control the movement of products from the company. In this study, the author uses COBIT 5 framework with sub domains APO01, BAI01, DSS01, MEA01 and EDM01. For the calculation of the average maturity level of the five sub domains, which is 432%, when viewed from the rating scale, it is included in level F which indicates that it has reached the Fully achieved value where there has been a complete and systematic approach and full achievement. And in terms of the rounding scale of the condition mapping index of the capability model, it is the Performed Process where the process of the SAP application system at PT. Kirana Windu has been successfully implemented and has achieved the goals planned by the institution. From the results of the calculation of the GAP or gap, it is known that for all domains the target level has been reached.